EKSPERIMENTASI MODEL PEMBELAJARAN PBL, MODEL PEMBELAJARAN KOOPERATIF TIPE TGT, DAN STAD DITINJAU DARI TINGKAT AKTIVITAS METAKOGNISI - Wahartojo, Sri; Budiyono, Budiyono; Usodo, Budi (Jurnal Pembelajaran Matematika, 2016)
Abstract: The purpose of this study was to know the effect of the learning models on the learning achievement in mathematics viewed from the students category of metacognition activity. The learning models compared were PBL learning model, the cooperative learning model of TGT, and STAD. The type of research was a quasi-experimental research with a 3x3 factorial design. The population of the study was all first grade students of Vocational High Schools in Surakarta in academic year 2015/2016 by using Curriculum 2013. Instruments used for data collection techniques were mathematics achievement test and questionnaire from metacognition activity. The data analysis technique used was the two-way ANOVA with unequal cell. Based on the hypothesis test, it was concluded that: 1) The mathematics learning achievement of TGT was better than PBL, the mathematics learning achievement of STAD was better than PBL. The mathematics learning achievement of TGT was equal STAD. 2) The mathematics learning achievement of the students with middle category in metacognition activity was better than the students with low category in metacognition activity. The mathematics learning achievement of the students with low category in metacognition activity was equal with the students who had high category in metacognition activity. The mathematics learning achievement of the students with middle category in metacognition activity was equal with the students who had high category in metacognition activity. 3) On all learning models, PBL learning model, TGT learning model, and STAD learning model, the mathematics learning achievement of the students with middle category in metacognition activity was better than students with low category, but the students with low category was equal with high category students then, middle category students was equal with high category students. 4) On all categories, the students with low, middle, and high category in metacognition activity who were treated by PBL, TGT, and STAD learning models, TGT was better than PBL, then, STAD was better than PBL, in addition TGT was equal with STAD.Key words: Achievement in Learning Mathematics, Metacognition Activity, PBL, STAD, TGT Learning Model.